Minimum Wages in Developing Countries : Helping or Hurting Workers? - Terrell, Katherine; Almeida, Rita K. (World Bank, Washington, DC, 2012)
This policy note reviews the literature on the effects of minimum wages on labor markets in developing countries. The authors begin by elucidating the challenges to ascertaining these effects, especially in developing economies where a large segment of the workforce is not covered by minimum wage legislation (uncovered sector). After summarizing the theoretical models and their predictions, the authors review the empirical evidence of the impact of minimum wage legislation on wages, employment, and unemployment in the covered and uncovered sectors of the labor market. The evidence strongly suggests that an increase in the minimum wage tends to have a positive wage effect and a small negative employment effect among workers covered by minimum wage legislation and that the effects tend to be stronger among low-wage workers. The findings are quite limited and fairly inconclusive on the indirect effects of increases in minimum wages on workers in the uncovered sectors, where the legislation either does not apply or is not complied with.